2008
DOI: 10.1007/s10164-008-0104-1
|View full text |Cite
|
Sign up to set email alerts
|

Nest orientation of the Spotted Barbtail, Premnoplex brunnescens, is strongly correlated with stream flow

Abstract: The placement and orientation of bird nests may strongly influence reproductive success. For many species, nest orientation is related to the cardinal directions and has to do with prevailing winds or solar exposure. Nest orientation differs among species in different environments, variously cooling or warming nests to maintain a nest microclimate optimal for successful development of eggs and young. The Spotted Barbtail (Premnoplex brunnescens) builds mossy, enclosed nests along shaded streams in Neotropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
5
0
3
Order By: Relevance
“…However, it is known that the phylogenetic proximity between species is also reflected in the structural similarity of nests, especially in Furnariidae (Zyskowsky and Prum 1999; Irestedt et al 2006; Ohlson et al 2013). Some studies conducted with Furnariidae nests have indicated that incubation chamber orientation does not always follow the same pattern, and that the same species may show structural changes according to the habitat conditions of each breeding season (Mezquida 2004; Greeney 2009). Of the three nests observed in our study, two oriented chamber opening to the north and east.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that the phylogenetic proximity between species is also reflected in the structural similarity of nests, especially in Furnariidae (Zyskowsky and Prum 1999; Irestedt et al 2006; Ohlson et al 2013). Some studies conducted with Furnariidae nests have indicated that incubation chamber orientation does not always follow the same pattern, and that the same species may show structural changes according to the habitat conditions of each breeding season (Mezquida 2004; Greeney 2009). Of the three nests observed in our study, two oriented chamber opening to the north and east.…”
Section: Discussionmentioning
confidence: 99%
“…to GONÇALVES, March 2015). It is known that nest orientation is interpreted as a response to microclimate conditions, especially wind direction and solar radiation (Yanes et al 1996; Mezquida 2004; Burton 2006; Greeney 2009). Overall, the collected information showed that Straight-billed Reedhaunter’s nest orientation tended to lie between north and east.…”
Section: Discussionmentioning
confidence: 99%
“…Nests are built in a wide variety of situations ranging from earthen or wooden cavities to suspended clumps of moss, almost exclusively directly over streams and below 5 m (Greeney 2008a). While the nest attachment method varies, the nests show very specific orientations that are directly related to the stream flow below the nest (Greeney 2008b). Two eggs, laid at 48-h intervals, are incubated by both parents for 27-31 days (Greeney 2008c).…”
Section: Introductionmentioning
confidence: 99%
“…For example, at high latitudes in the Northern hemisphere nests are usually oriented towards the equator, taking advantage of solar radiation to reduce cold temperatures (Landler et al 2014). In environments close to the equator, species are expected to orient their nests to maximize shade during the middle of the day, when the sun is highest and therefore daily temperatures are at their maximum (Greeney 2009, Van der Hoek 2017. At mid-latitudes, nest location may result from the compromise of having enough shading from above and from the western side (against midday and/or afternoon sun), and possibly facing east to warm more rapidly in the morning (Nelson & Martin 1999, Burton 2007.…”
Section: Introductionmentioning
confidence: 99%